Determinants of labor market participation choice of farm households in rural Ethiopia: multinomial logit analysis - Bedemo, A.; Getnet, Kindie; Kassa, B. (2013)
This paper examines the determinants of labor market participation decision of farm households in rural Ethiopia using sample household survey data collected from the study area. Factors affecting households' probability of participation in a particular labor market regime were analyzed using descriptive data and multinomial logit model. The overall result of the analysis indicated that farm households in the study area integrate into labor markets as buyers or sellers of labor. Specifically, the probability of a household to choose a particular labor market regime was related to initial differences in resource endowments, household composition and characteristics, farm attributes and location characteristics. The finding that households integrate into labor markets as buyers or sellers has considerable policy implications with regards to the distribution of benefits that may arise from policy interventions, were the rural labor market serves as a mechanism through which the distribution of benefits from such interventions are realized.